Design of ciprofloxacin-loaded nano-and microcomposite particles for dry powder inhaler formulations: preparation, in vitro characterisation, and antimicrobial efficacy. (18th August 2018) - Topal, Gizem Rüya; Devrim, Burcu; Eryilmaz, Müjde; Bozkir, Asuman
Abstract: In this study, ciprofloxacin hydrochloride (CIP)-loaded poly-ε-caprolactone (PCL) nanoparticles were prepared for pulmonary administration. CIP-loaded PCL nanoparticles were prepared using solid-in-oil-in-water (s/o/w) emulsion solvent evaporation method, and the effects of various formulation parameters on the physicochemical properties of the nanoparticles were investigated. PCL nanoparticles showed spherical shapes with particle sizes around 143–489 nm. Encapsulation efficiency was found to be very low because of water-solubility properties of CIP. However, the surface modification of nanoparticles with chitosan caused an increase in the encapsulation efficiency of nanoparticles. At drug release study, CIP-loaded PCL nanoparticles showed initial burst effect for 4 h and then continuously released for 72 h. Nanocomposite microparticles containing CIP-loaded PCL nanoparticles were prepared freeze-drying method and mannitol was used as carrier material. Tapped density and MMADt results show that nanocomposite microparticles have suitable aerodynamic properties for pulmonary administration. Antimicrobial efficacy investigations showed that CIP-encapsulated PCL nanoparticles and nanocomposite microparticles inhibited the growth of bacteria. Also, when the antimicrobial activity of the nanoparticles at the beginning and at the sixth month was examined, it was found that the structure of the particulate system was still preserved. These results indicated that nanocomposite microparticles containing CIP-loaded PCL nanoparticles can be used for pulmonary delivery.